MERAJUT HIDUP DARI BENGOK Pola-Pola Pemanfaatan Bengok (Eceng Gondok) Di Sekitar Danau Rawa Pening Dalam Perspektif Pembangunan Berkelanjutan. - Alvianto Wahyudi Utomo (Cakrawala Jurnal Penelitian Sosial, 2016)
Rawa Pening is one of the 500 lakes in Indonesia, but has the condition of ecologicaldemage quite severe when compared with other lakes. This is because of theuncontrollable weed water plants growth that covers most of the Lake Rawa Pening.Previous research shows, in 2002 weed water plants population in Lake Rawa Pening hasreached 20% - 30% surface its waters – or area of 150 Ha, and growing each year. Thereare efforts to control and eradicate the weed, but do not show significant result. On theother hand, there are people who take advantages of weed water plants to adequate theireconomic social life. They used with various patterns of utilization of giving substantialeconomic value themselves in accordance with the pattern of the utilization of that done.This research examines abaut the utilization of weed water plants or water plants orwater hyacinth, in the perspective of sustainable development concept, using qualitativemethods and types of research descriptive. The source of the data in this research issocieties that utilize water hyacinth as a source of their livelihood by doing observationand interview, beside supported with data skunder.The concept of sustainable development focus of the balance of economic aspects, socialand environment. The utilization of water hyacinth as craft products, and the utilizationof peat land as fertilizer or growing media fungus is expected to slightly resolve theproblem of ecological in Rawa Pening, besides give economic benefits and resolve socialissues, namely give jobs for the community.Keywords: Lake Rawa Pening, weed water plants or water hyacinth, Patterns ofuntilization of Water Hyancinth, Sustainable Development